How frequent is osteogenesis imperfecta in patients with idiopathic osteoporosis?: Case reports. Issue 35 (September 2017) - Al Kaissi, Ali; Windpassinger, Christian; Chehida, Farid Ben; Ghachem, Maher Ben; Nassib, Nabil M.; Kenis, Vladimir; Melchenko, Eugene; Morenko, Ekatrina; Ryabykh, Sergey; Hofstaetter, Jochen G.; Grill, Franz; Ganger, Rudolf; et al.
Abstract: Rationale: The term idiopathic osteoporosis itself is quite a non-specific disease label, which fails to address the etiological understanding. Bone mineral density alone is not a reliable parameter to detect patients at high risk of fracture. The diversity of the clinical phenotypes of discolored teeth, blueness of the sclera, back and joint pain, cardiovascular disease, Diabetes type II, hearing problems and a long list of orthopedic problems are have to be considered. Patients concerns: Our study has been designed in accordance with the clinical and radiological phenotype of eleven index cases with the provisional diagnosis of OI, which was followed by genotypic confirmation. This was followed by the invitation of siblings, parents, grandparents and other relatives to participate in the interviews, and to discuss the impact of the diagnosis. Proper collaboration with these families facilitated the process to identify other subjects with a history of fractures and other deformities/disabilities which were seemingly correlated to heritable connective tissue disorder. In total, 63 patients (27 children and 36 parents/grandparents and relatives) were enrolled in the study. Two groups of children were not included in our study. We excluded children with incomplete documentation and children who manifested de novo mutation. The term idiopathic osteoporosis (IOP) has been given to these families in other Institutes and was considered as a definite diagnosis. IOP was solely based on T scores, BMD and certain laboratory tests. Surprisingly, no single adult patient underwent clinical and or radiological phenotypic characterization. Diagnoses: A constellation of significant disease associations with osteoporotic fracture risk have been encountered. The index cases showed mutations in COL1A1 (17q21.31.q22) and COL1A2 (7q22.1), the genes encoding collagen type I. The phenotype/genotype confirmation in 11 children was the key factor to boost our research and to re-consult each family. Comprehensive clinical and radiological phenotypic documentation has been applied to most of other family subjects who principally received the diagnosis of IOP. Interventions: All adult patients had normal serum calcium and only three patients showed an average of low serum phosphate of 0.7–0.61 mmol/l. Serumcrosslaps in six parents was in the average of (2.9–3.8 nM) and PTH levels were normal in all patients (the average showed 8.73 pg/ml). Outcomes: Our efforts to minimize and constrain the usage of the term idiopathic osteoporosis and to understand the sequence of pathological events that occurred in these families were emphasized. These efforts evolved into a remarkable and unique constellation of clinical findings. Strikingly, fracture represented a portion in a series of skeletal and extra-skeletal deformities and abnormalities which are all correlated to connective tissue disorder. This was achieved mainly through comprehensive phenotype/genotype confirmation, followed by scrutinizing the records of each family, clinical examination of the adults and revising the archives of our Hospitals and other Institutes. Lessons: The sequence of diverse pathological events recorded within each family would be almost incomprehensible without a proper etiological understanding of the natural history of each child/family deformity that led to their occurrences. We wish to stress that, our current study is just an attempt to cover only a tiny fraction of the tip of the iceberg and to profoundly explore one of the most under-estimated causes of idiopathic osteoporosis.